The flower characteristics of a plant is one of the important traits correlated to its productivity. Study on flower characteristics is useful to understand how to increase the crop productivity. The research was conducted at Agro Techno Park Center, Indonesian State Ministry of Research and Technology, Bakung Village, Ogan Ilir Distric South Sumatra from April 2007 to August 2008. The objective of this research was to evaluate the flower characteristics and the yield of jatropha (Jatropha curc - ANDI WIJAYA; SUSANTI DIANA; MUHAMAD UMAR HARUN; HENY HAWALID (Bogor Agricultural University, Indonesia, 2009)
The flower characteristics of a plant is one of the important traits correlated to its productivity. Study on flower characteristics is useful to understand how to increase the crop productivity. The research was conducted at Agro Techno Park Center, Indonesian State Ministry of Research and Technology, Bakung Village, Ogan Ilir Distric South Sumatra from April 2007 to August 2008. The objective of this research was to evaluate the flower characteristics and the yield of jatropha (Jatropha curcas L.) accessions. The research was arranged in a randomized block design, consisted of fifteen accessions of jatropha, with three replicates. The Jatropha accessions were collected from different agro ecosystems located in Sumatra, Java, and Borneo. The results indicated that the evaluated accessions have significant differences in the flower characteristic and the yields. The ratio male–female flower is the most important character for J. curcas L. because it has a significant correlation to the yield. Key words: flower, yield, Jatropha curcas